The Medium-Term Effects of Scholarships in a Low-Income Country - Filmer, Deon (University of Wisconsin Press, 2022)
Despite progress in recent decades, a substantial fraction of children in developing countries attain little schooling, and many adults lack skills that are valued in the labor market. We evaluate the medium-term effects of a program that provided scholarships for three years to poor children upon graduation from elementary school in Cambodia, a low-income country. To do this we use a sharp regression discontinuity design. We show that scholarships have substantial effects on school attainment. By the time children would have been in grade 11 had they remained in school, two years after they stopped being eligible for scholarships, those who were offered scholarships have attained 0.6 more grades of completed schooling. Nevertheless, we find no evidence that scholarships had significant effects on test scores, employment, earnings, or the probability of getting married or having a child in adolescence.